Empowering professional learning communities: the role of middle leadership and teacher participation in decision-making - Yeap, Sock Beei; Md Ali, Nurul Jawahir (Institute of Advanced Engineering and Science, 2025)
Professional learning communities (PLCs) are essential for fostering collaboration and continuous school improvement. However, their implementation faces significant challenges, including passive teacher attitudes, limited understanding of PLCs, increased workloads, and ineffective execution by school communities. Addressing these challenges requires a supportive organizational structure that enhances PLCs effectiveness. This study aims to examine the effect of middle leadership (MLT) on PLCs. Specifically, this study also examines the mediating effect of teacher participation in decision-making (TM) on the relationship between MLT and PLCs. Data were collected from 284 secondary school teachers in Penang and analyzed using partial least squares structural equation modeling (PLS-SEM). The findings revealed that MLT had a significant effect on PLCs, and TM mediates the relationship between MLT and PLCs. This study provides valuable insights for policymakers and school leaders on fostering a collaborative school culture through effective MLT practices, ultimately strengthening PLCs implementation in Malaysian secondary schools. Furthermore, these findings underscore the significance of empowering teachers participation in decision-making to enhance PLCs effectiveness.